THE INFLUENCE OF WORK DISCIPLINE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT THE PUPR VIII COMPETENCY DEVELOPMENT CENTER FOR THE MAKASSAR REGION - Batari Khamila Jufri; Amiruddin Tawe; Muh. Ilham Wardhana Haeruddin; Agung Widhi Kurniawan; Uhud Darmawan Natsir (Transpublika Publisher, 2023)
In the dynamic landscape of current organizations, the performance of employees is a pivotal factor in achieving goals and maintaining competitiveness. A multitude of variables can significantly influence employee performance, with work discipline and work motivation being of particular importance. The Competency Development Center of PUPR VIII, located in the Makassar region, serves as the setting for this research, where the intricate interplay of these two variables on employee performance is investigated. This research seeks to ascertain the impact of work discipline and work motivation on employee performance within the ambit of the Competency Development Center of PUPR VIII, situated in the Makassar region. The research methodology employed is quantitative, utilizing a sample of 37 employees. Data analysis techniques encompass validity and reliability assessments, classical assumption tests, multiple linear regression analysis, T-tests, and F-tests. The findings of this study affirm a significant correlation between work discipline (X1) and work motivation (X2) and employee performance (Y), substantiated by T-test and F-test analyses. Furthermore, the results demonstrate that the F-value exceeds the tabulated F-value (0.000 < 0.005). The coefficient of determination, R-square, amounts to 0.494%, underlining the influence of these variables on employee performance.